Determinan Kepuasan Pengguna E-Wallet OVO dengan Keputusan Penggunaan Sebagai Mediasi - Natasya Afifah Salsabilah; Sri Murtiasih (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine the direct and indirect effects of ease of use and electronic word of mouth on user satisfaction, with the mediation of usage decisions among OVO e-wallet users. The population for this study consists of OVO e-wallet users in the Jabodetabek area in 2022. The sampling method used in this study is non-probability sampling with purposive sampling technique, involving 150 respondents. Data collection was done using an online Google Form questionnaire. The data were analyzed using IBM SPSS version 26 and AMOS version 26 software. The analysis method used in this study is Structural Equation Modeling (SEM), which includes validity testing, reliability testing, Confirmatory Factor Analysis (CFA), normality testing, outlier testing, model fit testing, and hypothesis testing.